2012
DOI: 10.1186/1471-2369-13-160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-sodium diet on renal tubule Ca2+transporter and claudin expression in Wistar-Kyoto rats

Abstract: BackgroundUrinary Ca2+ excretion increases with dietary NaCl. NaCl-induced calciuria may be associated with hypertension, urinary stone formation and osteoporosis, but its mechanism and long-term effects are not fully understood. This study examined alterations in the expressions of renal Ca2+ transporters, channels and claudins upon salt loading to better understand the mechanism of salt-induced urinary Ca2+ loss.MethodsEight-week old Wistar-Kyoto rats were fed either 0.3% or 8% NaCl diet for 8 weeks. Renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…This observation is also supported by Gibbs who reported that supercedance of hunger center by the thirst center during salt loading 42 can lead to increase in water intake with resultant net weight loss. 43 Same effects were seen by Yatabe 34 who demonstrated decrease in weight gain with significant result p˂0.05 after feeding high salt diet (0.8% NaCl) to a group of rats for eight weeks. This could be due to increased calcium excretion with subsequent volume expansion and competition between Na and Ca ions in proximal convoluted tubules.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This observation is also supported by Gibbs who reported that supercedance of hunger center by the thirst center during salt loading 42 can lead to increase in water intake with resultant net weight loss. 43 Same effects were seen by Yatabe 34 who demonstrated decrease in weight gain with significant result p˂0.05 after feeding high salt diet (0.8% NaCl) to a group of rats for eight weeks. This could be due to increased calcium excretion with subsequent volume expansion and competition between Na and Ca ions in proximal convoluted tubules.…”
Section: Discussionmentioning
confidence: 63%
“…21,34,35 Although, increase in the total body weight (RTBW) of all the groups during eight weeks was observed, rats in group C had highest weight gain of 54g followed by weight gain of 37g in experimental group B. Increase in weight was observed in both experimental groups but the least weight gain of 22g was observed in group A fed on high salt diet.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rizzo et al (20) found that bumetanide, a loop diuretic, upregulates CBD28k. Yatabe et al (25) reported that a high-sodium diet upregulates TRPV5, CBD-28k, and the Na/Ca exchanger (25). It has been suggested that the concerted upregulation of more distal Ca 2ϩ -and Mg 2ϩ -transporting molecules may be a physiological response to reduce the loss of Ca and Mg.…”
Section: Discussionmentioning
confidence: 99%
“…Urine was collected for 24 h using metabolic cages. Sodium, potassium, creatinine, plasma renin activity, plasma aldosterone concentration, and urinary protein concentrations were determined as described previously [14,15,16]. FGF23 concentration in serum or plasma was determined using FGF-23 ELISA kit (KAINOS Laboratories, Tokyo, Japan), and serum 1,25 (OH) 2 vitamin D concentration was determined by SRL, Inc. (Tokyo, Japan) using radioimmunoassay.…”
Section: Blood Pressure and Biochemical Analysismentioning
confidence: 99%